1991
DOI: 10.1042/cs0810305
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and tissue kallikrein–kinin systems during acute administration of frusemide in normotensive and hypertensive humans

Abstract: 1. This study aims to further elucidate the role of the tissue and plasma kallikrein-kinin systems in blood pressure, electrolyte and volume homoeostasis. Components thereof and of the renin-angiotensin-aldosterone system were measured in conjunction with frusemide administration, in normotensive subjects and in patients with primary hypertension. 2. Frusemide increased plasma pre-kallikrein, angiotensin II and aldosterone concentrations and plasma renin activity, whereas the plasma level of tissue kallikrein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In all patients, urinary hK1 amidase activity was reduced 19 . Ohman and Karlberg 20 observed that furosemide increases the urine volume and the excretion of tissue kallikrein in normotensive individuals and in patients with primary hypertension. Thus the diminished levels of hK1 amidase activity (instead of their expected increasing) in patients treated with furosemide, in our study, could be explained by their having HF 19 .…”
Section: El Figueiredo Et Al Human Tissue Kallikrein and Kinins In Shfmentioning
confidence: 99%
See 1 more Smart Citation
“…In all patients, urinary hK1 amidase activity was reduced 19 . Ohman and Karlberg 20 observed that furosemide increases the urine volume and the excretion of tissue kallikrein in normotensive individuals and in patients with primary hypertension. Thus the diminished levels of hK1 amidase activity (instead of their expected increasing) in patients treated with furosemide, in our study, could be explained by their having HF 19 .…”
Section: El Figueiredo Et Al Human Tissue Kallikrein and Kinins In Shfmentioning
confidence: 99%
“…Some experimental studies were published since our publication, regarding ischaemic HF. Spillmann et al 20 aimed to test the original hypothesis that hK1 gene delivery to the peri-infarct myocardium would prevent post-ischemic HF. They induced MI in anesthetized mice by permanently occluding the left coronary artery.…”
Section: El Figueiredo Et Al Human Tissue Kallikrein and Kinins In Shfmentioning
confidence: 99%